2022
DOI: 10.1101/2022.01.07.22268919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of mRNA-1273 against SARS-CoV-2 omicron and delta variants

Abstract: Background The recently emerged SARS-CoV-2 omicron variant raised concerns around potential escape from vaccine-elicited immunity. Limited data are available on real-world vaccine effectiveness (VE) of mRNA-1273 against omicron. Here, we report VE of 2 or 3 mRNA-1273 doses against infection and hospitalization with omicron and delta, including among immunocompromised individuals. Methods This test negative study was conducted at Kaiser Permanente Southern California. Cases were individuals aged ≥18 years test… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
191
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(213 citation statements)
references
References 19 publications
21
191
1
Order By: Relevance
“…This result is consistent with studies showing reduced neutralization efficiency of two and three doses of BNT162b2 vaccine against the Omicron variant (versus non-Omicron variants) [3,26]. Similarly, in multiple settings, vaccination with two doses showed slightly lower effectiveness against hospitalization with Omicron vs. Delta variant infections [6][7][8]. Our finding of higher relative protection against Delta variant infections is reassuring considering the greater severity observed in infections with the Delta variant as compared to the Omicron variant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This result is consistent with studies showing reduced neutralization efficiency of two and three doses of BNT162b2 vaccine against the Omicron variant (versus non-Omicron variants) [3,26]. Similarly, in multiple settings, vaccination with two doses showed slightly lower effectiveness against hospitalization with Omicron vs. Delta variant infections [6][7][8]. Our finding of higher relative protection against Delta variant infections is reassuring considering the greater severity observed in infections with the Delta variant as compared to the Omicron variant.…”
Section: Discussionsupporting
confidence: 90%
“…We have quantified two aspects of comparative severity of Omicron vs. Delta variant infections: the risk of progression to severe endpoints among diagnosed cases, and the risk of progression to acute respiratory symptoms among those first diagnosed before symptoms onset. While attenuation of disease severity in association with the Omicron variant is an encouraging finding, prior evidence of higher transmissibility of Omicron variant infections [27], as well as immune evasion from prior infection [28] and vaccination [68], are concerning. Rapid spread of the Omicron variant in a compressed time period has led to unprecedented surges in COVID-19 among our study population and others globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with in vitro studies that showed a 30–40-fold reduction in neutralisation of the Omicron variant compared with wild type when using convalescent sera or sera of individuals who had completed the primary vaccination series [ 5 - 7 ]. Several studies have reported a substantial reduction in vaccine effectiveness against infection with the Omicron variant compared with Delta after primary vaccination [ 13 - 16 ]. After booster vaccination, the vaccine effectiveness against infection with the Omicron variant increased but was still lower than against Delta [ 14 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 A reduction in neutralizing antibodies against Omicron following second and third doses of mRNA vaccines has been established, [4][5][6][7][8][9] but real-world data evaluating vaccine performance against Omicron infection are still emerging. [10][11][12][13][14][15][16][17][18] We previously estimated vaccine effectiveness (VE) against infection (irrespective of symptoms or severity) in the initial period following identification of Omicron in Ontario, in order to support urgent public health decisions. 19 At that time, data on symptoms were unavailable, and few cases involved hospital admission to evaluate severe outcomes.…”
Section: Introductionmentioning
confidence: 99%